2013
DOI: 10.1248/bpb.b12-00778
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of the Human Ether-à-go-go-Related Gene Channel by Imatinib Mesylate

Abstract: Imatinib mesylate (IM), a widely prescribed powerful tyrosine kinase inhibitor, has been associated with increased risk of heart failure and is known to induce cell apoptosis and death in isolated cardiomyocytes. In addition to acquired long QT syndrome, pharmacological inhibition of human ether-à-go-go-related gene (HERG) channel has been reported to involve in apoptosis. The present study was undertaken to characterize the biophysical properties of IM on HERG and the molecular determinants of HERG blockade u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Human embryonic kidney 293 (HEK 293) cells were cultured in the same condition as described above. HEK 293 cells were transiently transfected with appropriate cDNA plasmids using Lipofectamine LTX and PLUS (Invitrogen) method as described previously 50 . The cDNA encoding human Kv1.2 (from Prof. Yingliang Wu, Wuhan University, Wuhan, China), human Kv1.3 (generously provided by Dr. Garcia Maria, Merck & Co. Inc., West Point, PA, USA) and human Kv1.5 (from Prof. Guirong Li, Hongkong University, Hongkong, China) were subcloned into the vector of pIRES2-EGFP (Clontech, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Human embryonic kidney 293 (HEK 293) cells were cultured in the same condition as described above. HEK 293 cells were transiently transfected with appropriate cDNA plasmids using Lipofectamine LTX and PLUS (Invitrogen) method as described previously 50 . The cDNA encoding human Kv1.2 (from Prof. Yingliang Wu, Wuhan University, Wuhan, China), human Kv1.3 (generously provided by Dr. Garcia Maria, Merck & Co. Inc., West Point, PA, USA) and human Kv1.5 (from Prof. Guirong Li, Hongkong University, Hongkong, China) were subcloned into the vector of pIRES2-EGFP (Clontech, USA).…”
Section: Methodsmentioning
confidence: 99%
“…As with many drugs, tyrosine kinase inhibitors (TKIs) are reported to prolong the QT interval ( Strevel et al , 2007 ; Bello et al , 2009 ; Lee et al , 2010 ; Tolcher et al , 2011 ; Dogan et al , 2012 ; Doherty et al , 2013 ; Dong et al , 2013 ; Heath et al , 2013 ; Shah et al , 2013 ). In vitro studies demonstrated that lapatinib and imatinib interact with the phosphorylation of the cardiac hERG channel.…”
mentioning
confidence: 99%
“…In vitro studies demonstrated that lapatinib and imatinib interact with the phosphorylation of the cardiac hERG channel. This results in a reduction of the repolarising current (IKr), which can lead to action potential prolongation and subsequent QT-interval prolongation ( Lee et al , 2010 ; Dong et al , 2013 ).…”
mentioning
confidence: 99%
“…As mentioned, QT prolongation is more dangerous with bradycardia, so carefully monitoring in patients under the treatment of crizotinib is necessary. According to the formal studies, imatinib could preferentially block the open HERG channel, contributing to QT interval prolongation [ 65 ]. Lapatinib can block the HERG channel in transfected HEK293 cells and prolong the action potential duration [ 66 ], prolonging the QT interval.…”
Section: Novel Antineoplastic Drugsmentioning
confidence: 99%